Development of M-Learning Teaching Materials on Trigonometric Materials to Improve Mathematic Connection Ability - Poppy Yaniawati; Nenden Mutiara Sari; Na'immatur Rokhmah; Nurul Fitri; Suhayat Hadiansyah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
Abstract Teaching material is given to students and assists students in learning something and making learning more interesting and easy to understand. M-learning is a learning media containing teaching materials and can be accessed by students with more attractive visuals and improve student learning outcomes. This study aims to produce M-Learning teaching materials on trigonometry and analyze the improvement of the mathematical connection abilities of XI grade students after using these teaching materials. The approach in this research is a mixed method. The research design used in this study was the One-Group Pretest-Postest Design. This type of research is R&D (Research & Development). The instruments in this study were validation sheets, interviews, questionnaires, and mathematical connection ability tests, which were analyzed using t-test and N-gain and involved 26 students of class XI SMK Karya Pembangunan Pasirjambu Bandung. This study indicates that the M-Learning Application of valid (feasible) trigonometric material is used based on the validation assessment of media experts, material experts, and student responses. In addition, there are differences in the improvement of mathematical connection skills between before and after learning using M-Learning teaching materials. The results of this study indicate that the M-Learning Application of trigonometric material is valid (appropriate) to be used based on the validation assessment of media experts, material experts, and student responses. In addition, there are differences in the improvement of mathematical connection skills between before and after learning using M-Learning teaching materials. The results of this study indicate that the M-Learning Application of trigonometric material is valid (appropriate) to be used based on the validation assessment of media experts, material experts, and student responses. In addition, there are differences in the improvement of mathematical connection skills between before and after learning using M-Learning teaching materials.